PEMBERDAYAAN IBU REMAJA MELALUI PELATIHAN SELF-ESTEEM DAN PEMBUATAN ABON IKAN DI NUSA TENGGARA TIMUR - Enjelita Mariance Ndoen; Helga Jilvera Nathalia Ndun (P3M Universitas Aisyiyah Surakarta, 2022)
Adolescent pregnancy remains a major issue in terms of health and social as it relates to morbidity and mortality of mothers and children. Therefore, a more holistic approach is required to support adolescent mothers to have a better quality of life. This empowering project, conducted in Oelasin Village, Southwest Rote, NTT was to empower psychologically and economically 20 adolescent mothers to have a normal life again and a chance of having equal position in household. Three days of an intensive self-esteem building program was undertaken to restore the self- esteem of the 20 participants and to improve their ability to cope with stigma and motherhood. The training consisted of three main activities, such as self-esteem materials and exercises, interpersonal counseling, and sharing experiences. The training was then followed with shredded fish (abon ikan) making training as an economic empowerment training that provided a sustainable relevant skill for the participants to generate income.Â At the final stage, participants joined in eight months of mentoring on shredded fish production and promotion activities. Through the participation in this project, the 20 teenage mothers are empowered to build a better quality of life for themselves and their families, and their environment in general.